2013
DOI: 10.1186/ar4281
|View full text |Cite
|
Sign up to set email alerts
|

Gout impacts on function and health-related quality of life beyond associated risk factors and medical conditions: results from the KING observational study of the Italian Society for Rheumatology (SIR)

Abstract: IntroductionGout is the most prevalent arthritis and significantly impacts on function and quality of life. Given that gout associates with disabling comorbid conditions, it is not clear whether such a complex of diseases accounts for the increased disability or if gout may play a role by itself. This study aims to evaluate the specific influence of gout and disease-related features on functional disability and health-related quality of life (HRQoL) in patients with gout followed in rheumatology clinics.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 30 publications
7
44
2
4
Order By: Relevance
“…This suggests that gout severity, in this case a combination of several poor gout characteristics, influences mental health. In particular, currently experiencing a gout attack has been associated with poorer general mental health in gout patients previously [20]. As our findings were not maintained after this adjustment, this suggests that though frequently experiencing attacks may contribute to some gout patients experiencing anxiety or depression, it alone is not enough to lead to these mental health comorbidities.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…This suggests that gout severity, in this case a combination of several poor gout characteristics, influences mental health. In particular, currently experiencing a gout attack has been associated with poorer general mental health in gout patients previously [20]. As our findings were not maintained after this adjustment, this suggests that though frequently experiencing attacks may contribute to some gout patients experiencing anxiety or depression, it alone is not enough to lead to these mental health comorbidities.…”
Section: Discussioncontrasting
confidence: 45%
“…However, when classification by gout characteristics was applied, such as by the number of painful joints [18], number of attacks in a 12-month period [14,[18][19][20] or disease duration [20], associations were found between gout and poorer general psychological health (as measured using the SF12 or SF36). This suggests that different gout characteristics may be important in identifying those patients more likely to experience poorer psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that after adjusting for potential medical and socio-demographic confounders, gout was an independent predictor for lower quality of life and functional outcomes. 14 This study was, however, performed using gout patients from rheumatology clinics rather than the general population. Gout patients with frequent flares and the presence of tophi have lower HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…В частности, группой итальянских ученных во главе с C.A. Scire была выполнена серия исследований [23,24], направленных на определение влияния клини-ческих проявлений подагры и сопутствующих заболева-ний на исходы подагры. Авторы выделили 10 клиниче-ских показателей прогностически тяжелой болезни.…”
Section: Discussionunclassified